Integrating Science, Faith, and Research in Islamic Excellence Schools - Adiyono Adiyono; Agus Zaenul Fitri; Ahmad Tanzeh (Academicus: Journal of Teaching and Learning, 2026)
This research is motivated by the demands of Islamic education transformation in the era of globalization that requires the integration of modern science and Islamic values ​​in a holistic and adaptive manner. The aim is to analyse how the educational model at MAN Insan Cendekia Paser is designed, implemented, and impacts the quality of graduates. This research aims to identify the main characteristics of an integrative educational model that is capable of producing graduates who excel academically while possessing moral and spiritual integrity. The method used is a qualitative approach with a case study design, through data collection techniques such as in-depth interviews, observation, and documentation, which are analysed using thematic analysis techniques. The results show that the success of this educational model is supported by the synergy between an integrative curriculum, a strong academic culture, a 24-hour coaching-based boarding school system, and the application of research-based learning that encourages the development of critical thinking skills, creativity, and problem-solving. In addition, this model has been proven to be able to produce globally competitive graduates without losing their Islamic identity. In conclusion, the MAN Insan Cendekia Paser educational model represents a new paradigm of Islamic education that is holistic, integrative, and future-oriented, and has the potential to be replicated as a model for developing superior madrasas at the national and international levels.